Oral pH value predicts the incidence of radiotherapy related caries in nasopharyngeal carcinoma patients - Zheng Li (Nature Portfolio, 2021)
Abstract Radiotherapy-related caries is a complication of radiotherapy for nasopharyngeal carcinoma; however, factors influencing the occurrence, accurate prediction of onset, and protective factors of radiotherapy-related caries remain unclear. This study analyzed risk factors, disease predictors, and protective factors for radiotherapy-related caries in nasopharyngeal carcinoma. This prospective study included 138 nasopharyngeal carcinoma patients receiving radical radiotherapy at our hospital during June 2012–December 2016 and were followed up for dental caries. Patients’ clinical data on radiotherapy were collected, dynamic monitoring was performed to assess changes in oral pH values, and a questionnaire survey was administered to collect patients’ lifestyle habits. Time-dependent cox regression trees, event-free Kaplan–Meier curve, Mann–Whitely U test were used to analysis the results. The median follow-up time was 30 (12–60) months. Radiotherapy-related caries occurred in 28 cases (20.3%). Univariate analyses showed that radiotherapy-related caries was associated with patient’s age, oral saliva pH value, green tea consumption, and radiation dose to sublingual glands, but not with the radiation dose to the parotid and submandibular glands. Multivariate analysis showed that oral saliva pH value [hazard ratio (HR) = 0.390, 95% confidence interval = 0.204–0.746] was an independent prognostic factor for radiotherapy-related caries. Patients with oral saliva pH values ≤ 5.3 in the 9th month after radiotherapy represented a significantly higher risks for radiotherapy-related caries (p < 0.001). Green tea consumption was associated with the occurrence of radiotherapy-related caries, and oral saliva pH values could predict the occurrence of radiotherapy-related caries. Limiting radiation doses to sublingual glands can reduce the occurrence of radiotherapy-related caries.